Pengembangan Talenta Unggul Melalui Training dan Development: Implementasi Human Capital Management di PT Yakult Indonesia Persada sebagai Bentuk Pengabdian kepada Masyarakat - Muhammad Abdullah Mafahir; Nofi Puji Lestari; Ferdiyan Yefta Melkisua Berelaka; Agustina Puji Nilamsari; Adhelia Ayu Putri; Heri Usodo (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Through the Field Work Lecture (KKL) program at PT Yakult Indonesia Persada, this community service activity was carried out with the aim of providing practical experience for students related to the implementation of Human Capital Management (HCM) in the industrial world. This program not only aims to provide theoretical insight, but also introduces students to the application of important concepts in human resource management in companies. The focus of the activity covers various aspects, such as the recruitment process, training programs and career development, and the reward system implemented at PT Yakult. This activity also provides an understanding of the important role of HCM in improving company performance through effective employee management. The results of the activity show that PT Yakult has developed a continuous training pattern aimed at improving employee competencies as a whole. In addition, the company also conducts employee talent mapping that allows for a systematic career path, which provides development opportunities for each individual within the company. The benefits obtained by students from this activity are not only increased knowledge of HCM, but also strengthened analytical skills, developed professional attitudes, and preparedness to face challenges in an increasingly dynamic workplace. Therefore, this KKL program is a very important tool for building stronger synergy between universities and the industrial world, so that students can be better prepared and competent in facing the ever-growing needs of industry.